REALITAS KESADARAN MASYARAKAT JAWA TENGAH AKAN PROKES PASCA COVID- 19 - Caroline Caroline; Rr Retno Sugiharti (CV. ADIBA AISHA AMIRA, 2024)
The behavior and adherence of the people of Central Java to health protocols will bring changes to a good and healthy lifestyle for the future of Central Java. Research on community behavior regarding post-covid-19 health protocols has never been done. This research is an extension of Caroline's (2021) research using data from Central Java BPS. The problem of this research is how the behavior of the people of Central Java after the covid-19 pandemic is over. The purpose of this study was to analyze how the behavior of the people of Central Java towards the Health Protocol after the Covid-19 Pandemic. This research is a research using qualitative questions with quantitative answers in the form of a Likert scale. This research method uses an online questionnaire approach. The conclusion from this study is that the people of Central Java with college education, the majority of whom are women, have a higher level of compliance than those with high school education and below in implementing health protocols, both in wearing masks, washing hands with soap/hand sanitizer, maintaining distance, and avoiding crowds, awareness of social distancing in Central Java is the lowest among other health protocols. It was identified that the people of Central Java who had been vaccinated against 1, 2, and booster vaccines had a higher level of adherence to health protocols.